Pengaruh Ecological Knowledge, Cognitive Skill, dan Environmental Affective terhadap Keterampilan Pemecahan Masalah Siswa SMA pada Materi Pemanasan Global dan Pencemaran Lingkungan - Adika Muhammad Aziz; Mimin Nurjhani Kusumastuti; Taufik Rahman (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The purpose of this study was to investigate the simultaneous and partial effects of ecological knowledge, cognitive skills, and environmental affective on problem-solving skills. Focusing on high school students in Cianjur Regency, grade 10, 66 students were selected using cluster random sampling as the sample. The research instruments included 15 essay questions on problem-solving skills, 10 multiple-choice questions on ecological knowledge, 7 questions on cognitive skills, and 15 items assessing environmental affective attitudes. Using multiple linear regression statistical analysis, the results showed no simultaneous influence of ecological knowledge, cognitive skills, and environmental affective factors on problem-solving skills, as evidenced by a significance value of 0.340. Additionally, the results showed no partial influence of each variable on problem solving skills. Statistical analysis also indicated that ecological knowledge, cognitive skills, and environmental affective only contributed 0.6% to problem-solving skills in the context of global warming and environmental pollution. Based on these research results, environmental literacy skills such as ecological knowledge, cognitive skills, and environmental affective skills in the context of global warming and environmental pollution are insufficient to develop good problem-solving skills. Therefore, problem-solving skills must still be trained even if students' environmental literacy skills are already sufficiently good.